Durvalumab-induced organizing pneumonia in extensive-stage small cell lung cancer: A case report and literature review - Guoxin Wang, MD; Wenjie Yan, MD; Jun Cai, MD; Fang Zhang, MD; Tangfeng Lv, MD; Mingxiang Ye, MD, PhD (Radiology Case Reports)
The etoposide-carboplatin and anti-PD-L1 combination has become the standard-of-care for patients with extensive-stage small cell lung cancer (ES-SCLC). This combinational strategy is well tolerated with manageable immune-related adverse effects (irAEs). In this report, we presented a rare immediate irAE after one course of anti-tumor treatment. The patient with ES-SCLC was treated with first-line etoposide-carboplatin chemotherapy and Durvalumab immunotherapy. After one cycle of indicated treatment, the patient developed persistent high-grade fever with extensive consolidation, surrounding by ground glass opacifications. The lesions did not respond to empirical antibiotics and the results for pathogen testing were negative. Histological analysis of biopsy sample yielded organizing pneumonia that was very likely to associate with Durvalumab treatment. The patient was therefore treated with prednisolone that resulted in a rapid radiological improvement. The reporting of this case is imperative for informing acute onset of irAE in patients with ES-SCLC treated with anti-PD-L1 immunotherapy. Differential diagnosis of infection, tumor progression and exacerbation of underlying illness should be considered before the initiation of prednisolone therapy.